2010
DOI: 10.1111/j.1439-0329.2009.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungi associated with the fir bark beetle Cryphalus piceae in Poland

Abstract: The aim of this study was to identify fungi associated with Cryphalus piceae on European silver fir (Abies alba) in Poland and to test the pathogenicity of selected isolates. Fungi were isolated from five populations of overwintered adults and their galleries. A great diversity of taxa was associated with C. piceae. In total, 2487 isolates, including 58 species distributed in 25 genera, were obtained. The two most frequently isolated fungi, an undescribed species of the genus Geosmithia and Ophiostoma piceae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
6
17
3
1
Order By: Relevance
“…In this study, S. polyspora has been isolated from the bark beetles and galleries of T. yunnanensis , which showed that S. polyspora could associate to T. yunnanensis in its lifecycle stage. This finding appears to supplement previous research (Jankowiak & Kolařík, ; Jankowiak & Rossa, ; Jankowiak et al., ). Our finding also indicates that S. polyspora has an association with bark beetles but not specifically with the species.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, S. polyspora has been isolated from the bark beetles and galleries of T. yunnanensis , which showed that S. polyspora could associate to T. yunnanensis in its lifecycle stage. This finding appears to supplement previous research (Jankowiak & Kolařík, ; Jankowiak & Rossa, ; Jankowiak et al., ). Our finding also indicates that S. polyspora has an association with bark beetles but not specifically with the species.…”
Section: Discussionsupporting
confidence: 90%
“…It has also been reported from a variety of conifers as the hosts of (Smerlis, 1970;Talgø et al, 2010). The present study demonstrates that S. polyspora is able to colonize and utilize P. (Jankowiak & Kolařík, 2010;Jankowiak & Rossa, 2008;Jankowiak, Rossa, & Mista, 2007). In this study, S. polyspora has been isolated from the bark beetles and galleries of T. yunnanensis, which showed that S. polyspora could associate to T. yunnanensis in its lifecycle stage.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Three representative ITS rDNA sequences (Hulcr12051 and LL84) were 100% identical to the hypocrealean fungus Sarocladium strictum and an uncultured Acremonium (GenBank accessions KM249080 and HG936339, respectively). Sarocladium has previously been reported to be associated with bark and ambrosia beetles throughout the northern temperate region (Hutchison 1999;Jankowiak et al 2007;Jankowiak & Kolařík 2010), as well as from mites Steneotarsonemus spinki Smiley (Acari: Tarsonemidae) in Taiwan (Hsieh et al 1980). Acremonium sp.…”
Section: Distribution Host Records and Symbiotic Fungi Of Euwallacementioning
confidence: 99%
“…oraz Pityokteines spp. Owady te s¹ zwi¹zane z ró¿nymi grzybami siniznowymi oraz grzybami z rodzaju Geosmithia (Jankowiak, Kolaøík 2010;Perenek et al 2008). Wyniki dooewiadczenia infekcyjnego przeprowadzonego w Polsce wskazuj¹, ¿e grzyby te s¹ saprotrofami lub s³abymi patogenami jod³y (Jankowiak, Kolaøík 2010).…”
Section: Wstêpunclassified